2022
DOI: 10.1002/advs.202205048
|View full text |Cite
|
Sign up to set email alerts
|

On‐Off Phagocytosis and Switchable Macrophage Activation Stimulated with NIR for Infected Percutaneous Tissue Repair of Polypyrrole‐Coated Sulfonated PEEK

Abstract: Intelligent control of the immune response is essential for obtaining percutaneous implants with good sterilization and tissue repair abilities. In this study, polypyrrole (Ppy) nanoparticles enveloping a 3D frame of sulfonated polyether ether ketone (SP) surface are constructed, which enhance the surface modulus and hardness of the sulfonated layer by forming a cooperative structure of simulated reinforced concrete and exhibit a superior photothermal effect. Ppy-coated SP could quickly accumulate heat on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Therefore, it is a new idea to obtain materials with adaptive sequential macrophage polarization through metabolic reprogramming. Our previous work fabricated the polypyrrole modified surface on PEEK, which could sequentially regulate macrophage phenotype through controlling NIR stimuli [ 5 ]. In this work, L-Arg was loaded onto the porous sulfonated PEEK surface to acquire adaptively sequential macrophage phenotype regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is a new idea to obtain materials with adaptive sequential macrophage polarization through metabolic reprogramming. Our previous work fabricated the polypyrrole modified surface on PEEK, which could sequentially regulate macrophage phenotype through controlling NIR stimuli [ 5 ]. In this work, L-Arg was loaded onto the porous sulfonated PEEK surface to acquire adaptively sequential macrophage phenotype regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Polyetheretherketone (PEEK) is an FDA-approved implant that can be used clinically as interbody fusion devices, bone implant, spinal fusion devices, etc, due to its good biocompatibility, closed elastic modulus, and corrosion resistance [ 3 ]. In our previous work, sulfonation was applied to construct a porous structure on PEEK surface, and the subsequent works verified that sulfonated PEEK could be a good drug delivery platform due to its superior stability in vivo [ [4] , [5] , [6] , [7] , [8] , [9] ]. Therefore, it is a good choice to choose PEEK as one of the candidates for percutaneous implantation.…”
Section: Introductionmentioning
confidence: 99%
“…First, a biomedical polyetheretherketone (PEEK) was employed as a substrate to construct a 3D network metastructure on PEEK, which is in accordance with our previous work. [50] The sulfonation time is 2 min (SP2), 5 min (SP5), and 15 min (SP15), respectively. The constructed SP15 porous coating exhibited excellent ATC performance.…”
Section: Sonothermal Property Of the Metastructure Coatingmentioning
confidence: 99%
“…Previous studies also demonstrated that the phagocytic activity and M1 polarization of macrophages went through a transient status when physical stimulation was removed. [31,32] The activated macrophages were then challenged with S. aureus to test their phagocytic ability (Figure 4i). The bacteria were pre-labeled with pHrodo dye so that phagocytosed S. aureus inside the cells can light up green.…”
Section: Phagocytosis Of Macrophages Against S Aureusmentioning
confidence: 99%